Congenital Heart Disease After the Fukushima Nuclear Accident: The Japan Cardiovascular Surgery Database Study - Yasutaka Hirata; Hideyuki Shimizu; Hiraku Kumamaru; Shinichi Takamoto; Noboru Motomura; Hiroaki Miyata; Yutaka Okita (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2020)
Background In March 2011, the Fukushima Daiichi nuclear power plant disaster inflicted radiation damage across the Tohoku region of Northern Japan. The consequent harm to pregnant mothers and newborns was a matter of concern. We performed a registry‐based analysis of the incidence of congenital heart disease during 2010 to 2013 using the Japan Cardiovascular Surgery Database. Methods and Results We selected patients who had complex congenital heart disease and who were born between January 1, 2010 and December 31, 2013 undergoing surgery, and assessed the trend in the number of first‐time surgeries performed for patients aged 2 years and younger by birth year over time. The numbers of first‐time surgeries for birth years 2010 to 2013 were 2978, 2924, 3077, and 2940, and no increasing trend was detected. Additionally, no increasing yearly trend was detected when the number of cases was divided by the total number of births in Japan in each birth month. The mortality of first‐time surgeries performed for complex diseases, which often involves multiple subsequent surgeries, decreased from 4.7% in 2010 to 2.2% in 2013. Conclusions Our analyses showed no increase in the number of patients with congenital heart disease during 2010 to 2013. The yearly increase in the total number of surgeries following the Fukushima Daiichi nuclear disaster in a previous report can be explained by the decline in the mortality of first‐time surgeries for complex cases. Such use of only the increase in the total yearly number of surgeries to claim the effects of a nuclear disaster on the incidence of congenital heart disease is a far too simplistic and dangerous proposition.